Exploration of the Creative Potential of Scheduled Caste Students With Ref to Five Sub-Tests of Language Creativity: Examining the Impact of Demographic Variables on Fluency Dimension of Creativity among Scheduled Caste Students (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Fluency is the ability of person to produce number ofrelevant and unrepeated ideas. Relevance is judged on the basis of theappropriateness of the response when considered in relation to the test problemand an unrepeated idea is one which has been expressed only once under givenproblem. There are certain myths in the social setup thatdemographic variables affect the level of fluency dimension of creativity. Toascertain this myth whether the demographic variables have any impact on thefluency dimension of creativity of the scheduled caste students, thesignificance level has been calculated by applying t-test and F-test  the results have been presented in the Table4.1.1